Migration of Brodifacoum and Diphacinone from Bait Pellets Into Topsoil at Palmyra Atoll National Wildlife Refuge - Alifano, Aurora; Wegmann, Alex; Puschner, Birgit; Howald, Gregg (Proceedings of the Vertebrate Pest Conference, 2012)
Between June 1 and 30, 2011, a partnership between the U.S. Fish and Wildlife Service, The Nature Conservancy, and Island Conservation successfully implemented a project to remove introduced black rats from Palmyra Atoll National Wildlife Refuge. Prior to the rat eradication, we assessed several environmental risk factors associated with the application of an anticoagulant rodenticide to Palmyra’s emergent land area. Here, we present the findings from a study of toxicant migration from bait pellets into topsoil. Topsoil from plots characterized as “sandy” or “humus” was collected after exposure to bait pellets containing 50 ppm of diphacinone or 25 ppm of brodifacoum. Brodifacoum and diphacinone were detected in samples of both sandy and organic topsoil while control samples collected outside of the study plots tested negative for both toxicants. With both toxicants, residue concentrations decreased with time and neither toxicant was detected in most of the 28, 36, and 50-day samples; trace amounts (=0.2 ppm for brodifacoum and =2 ppm for diphacinone) of the toxicants were detected in a few samples from these groupings. We did not find a significant difference in toxicant concentrations between the two types of topsoil. The results from this study suggest that following a broadcast of rodenticide across Palmyra’s emergent land area, small amounts of brodifacoum or diphacinone would migrate to, and remain in, Palmyra’s topsoil for a short period of time.